2018
DOI: 10.1002/jcph.1068
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of the TNF‐α and IL‐17A Dual‐Variable Domain Antibody ABT‐122 in Healthy Volunteers and Subjects With Psoriatic or Rheumatoid Arthritis: Analysis of Phase 1 and 2 Clinical Trials

Abstract: ABT-122 is an IgG1 dual-variable domain immunoglobulin that specifically blocks TNF-α and IL-17A. This work characterized ABT-122 pharmacokinetics using nonlinear mixed-effects modeling and ABT-122 serum concentrations from 72 healthy subjects, 196 subjects with rheumatoid arthritis (RA), and 144 subjects with psoriatic arthritis (PsA) enrolled in 4 phase 1 and 2 phase 2 studies (0.1-10 mg/kg intravenously and 0.3-3 mg/kg subcutaneous single doses and 0.3-3.0 mg/kg subcutaneous and 60-240 mg subcutaneous doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…37 The PK properties of JNJ-61178104 following SC administration were consistent with those of COVA322 and ABT-122 in phase 1 studies, and similar to typical mAbs administered by the SC route. 25,34,35 Additionally, the bioavailability and t max values of the JNJ-61178104 parental compounds were comparable to these observations at similar dose levels in normal healthy volunteers.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…37 The PK properties of JNJ-61178104 following SC administration were consistent with those of COVA322 and ABT-122 in phase 1 studies, and similar to typical mAbs administered by the SC route. 25,34,35 Additionally, the bioavailability and t max values of the JNJ-61178104 parental compounds were comparable to these observations at similar dose levels in normal healthy volunteers.…”
Section: Discussionsupporting
confidence: 73%
“…However, it has been suggested that having antigen-binding sites toward TNFα and IL-17A together may contribute to acceleration of clearance of these compound. 25,34,35 The half-life of JNJ-61178104 (4.3-9.7 days) was notably short when compared to its parental mAbs, JNJ-54160444 and golimumab, which were approximately 14.6 (±3.19) days and 12.23 (±2.90) days, respectively, following 1 mg/kg single doses in normal healthy volunteers. Relatively short half-lives have been previously reported for other bispecific antibodies that target TNFα and IL-17A, including COVA-322 and ABT-122 bispecific compounds following single IV doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of subjects with C trough concentrations below the limit of quantitation at the 12-week time point was~3% in both the ABT-122 120 mg every week and ABT-122 240 mg every week groups. Details of ABT-122 pharmacokinetic results are reported elsewhere (42).…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the amino acid sequences, the disulfide linkages, and the glycosylation patterns are similar to those of naturally occurring immunoglobulin G1 (IgG1) antibodies. A DVD‐Ig that binds and inhibits human TNF‐α and IL‐17A (ABT‐122) was developed, exhibited target engagement, and demonstrated efficacy in RA and psoriatic arthritis . However, ABT‐122 has shown faster clearance (14.4–30.9 mL/h for intravenous administration; apparent serum clearance [CL/F], 34.0–49.9 mL/h for subcutaneous administration), and a relatively higher incidence of antidrug antibodies (ADAs, 19%–99% in healthy subjects or adult patients with RA or psoriatic arthritis) than has been shown for other IgG1 monoclonal antibodies such as adalimumab (clearance, 12–17 mL/h for intravenous administration; CL/F, 28 mL/h for subcutaneous administration; and ADA incidence, 3%–10% in adult patients with RA, psoriasis, psoriatic arthritis, or hidradenitis suppurativa) .…”
mentioning
confidence: 99%